Penggunaan Media Kuartet Cerdas untuk Meningkatkan Hasil Pembelajaran PKN di SD - Widi Nursyamsi Apriawan; Nana Ganda; Syarip Hidayat (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The learning outcomes of fourth grade students at SDN 2 Sadapaingan, Panawangan District, Ciamis Regency, in understanding the meaning of the relationship between symbols and the Pancasila precepts are still low. This is because the learning interactions delivered by the teacher do not use the right media, so to overcome these problems, the "Kuartet Cerdas" media used is  determined to build better student learning outcomes. This study uses the spiral models Kemmis and MC Taggart. From the results of research on student learning activities, so that basic information on data collection from 13 students can be collected, only 5 students (38%) have finished getting a score above the KKM, which is 70. In the first cycle, 7 students obtained a complete result of (54%), in the second cycle 10 students obtained a complete result of (77%), and in the third cycle 12 students obtained a complete result of (92%) so that it exceeded the normal target of 80%. It can be concluded that through the use of the media "Kuartet Cerdas" can further develop the learning outcomes of students in Civics subject matter to understand the meaning of the relationship between symbols and Pancasila precepts.